Knee Extensor Apparatus Reconstruction with Allograft after Patellar Resection: A Case Report - Cosseddu, Fabio; Cordoni, Martina; Bechini, Elena; Ipponi, Edoardo; Campo, Francesco Rosario; D'Arienzo, Antonio; Andreani, Lorenzo (Acta medica Lituanica, 2024)
Background: The extensor apparatus of the knee can be thought of a chain that transmits the muscular strength developed by the quadriceps muscles to the proximal tibia. This complex is essential to allow the extension of the tibia over the femur, being essential to provide knee mobility and stability. In case of lesions which irreparably damage the patella, such as a locally aggressive bone tumor, it is necessary to restore both the apparatus’ anatomical continuity and its strength.Case report: A 39-years-old Caucasian man with a history of lung carcinoma developed atraumatic swelling and soreness in his left knee. Imaging evidence reported a degeneration of the left patella. We performed an en bloc resection of the patella and the nearby soft tissues of the extensor apparatus. The resulting gap was fulfilled with a massive allograft consisting of a quadriceps tendon, a patella and a patellar ligament. No complication or local recurrences were observed. At the patient’s latest follow-up, he did not have any extension lag and quadriceps strength was completely restored.Conclusion: Massive allografts can represent a reliable alternative for the reconstruction of the patella and the knee extensor apparatus in orthopedic oncology.
Keywords: Extensor Apparatus; Patella; Bone Metastasis; Allograft; Rehabilitation